2005
DOI: 10.1002/ptr.1767
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis and biological screening of leaf and twig extracts fromKunzea ericoides

Abstract: Kunzea ericoides is a member of the Myrtle group of tea trees. Leaf and twig material of K. ericoides was extracted with different solvents to afford terpene (including the essential oil), flavonoid and lipid classes (but no alkaloid class), which were subsequently screened for antibacterial, antitumour, cytotoxic, antioxidant and antiinflammatory activity. Differences were observed in the biological activity for the chemical classes tested, and in general, the leaf extracts were comparatively more bioactive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…At the end of the 72‐h incubation, over 80% cell death of L‐cells and Hep‐2 cells were observed for all temperature levels while 55–75% cell death was recorded for RD cells. Similarly, anticancer properties of kānuka leaf and twig extracts had been reported but for mouse tumour cells and rat hepatocytes 14 . Interestingly, in our study, some of these responses were biphasic with a low‐dose stimulation and high dose inhibition, a phenomenon called hormesis.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…At the end of the 72‐h incubation, over 80% cell death of L‐cells and Hep‐2 cells were observed for all temperature levels while 55–75% cell death was recorded for RD cells. Similarly, anticancer properties of kānuka leaf and twig extracts had been reported but for mouse tumour cells and rat hepatocytes 14 . Interestingly, in our study, some of these responses were biphasic with a low‐dose stimulation and high dose inhibition, a phenomenon called hormesis.…”
Section: Resultssupporting
confidence: 79%
“…Attempts to transfer this knowledge to modern application are seen through a few generalised in vitro studies, which support kanuka's anti‐inflammatory, 8,9 antimicrobial, 10 antiviral, 11 spasmogenic and spasmolytic, 12 and immunomodulatory 13 properties. Bioactivity‐guided experiments revealed that kānuka leaf extracts exhibited valuable biological activities 14 . However, these extracts were obtained using solvent extraction with ethyl acetate, ammonia methanol, dichloromethane, and isopropanol extraction, which all have associated drawbacks that cause concern for consumers and sustainable processing.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial and antifungal activity of several plants have been attributed to terpenoids (Wyatt et al, 2005;Filipowics et al, 2003) and phenolics (Heinonen, 2007) such as tannin, responsible for the astringent taste of P. edulis leaves. Despite of the fact that these classes of compounds had shown antibiotic activity against some types of strains (Heinonen, 2007;Kim, Shin, 2004;Kubo, Muroi, Kubo, 1993) …”
Section: Resultsmentioning
confidence: 99%
“…Besides these common techniques, two-dimensional NMR techniques (2-D NMR such as correlation spectroscopy-COSY, nuclear Overhauser effect spectroscopy-NOESY, heteronuclear single quantum coherence-HSQC, and heteronuclear multiple bond correlation-HMBC) have been used for the identification of artemceramide-D [73] and glyceroglycolipids [72]. Other methods are regularly used for the analysis of lipid extracts or their fractionation, such as TLC [57,69,74,77], column chromatography as mentioned above, or paper chromatography, but the information is very limited [69]. Analysis of FA is mostly performed by GC-FID or GC-MS, after derivatization.…”
Section: Extraction and Isolation Of Plant Lipidsmentioning
confidence: 99%